Learner Centered Instructional Methods and Observable Academic Competencies in Kiswahili Language among Secondary School Students in Mbarara Municipality, Uganda - Arishaba, Emilly; Balimuttajjo, Sudi (Journal of Research Innovation and Implications in Education, 2024)
Effective use of instructional methods can greatly develop learners’ observable academic competencies in the Kiswahili language. The average pass falling between D1 to C4 in Kiswahili language stood at a pass-rate of 40 % and below out of the 89% pass-rate expected by UNEB (UNEB, 2017). This poor performance has been blamed on the poor teaching styles. However, no empirical study has been carried out to determine the effect of learner-centred instruction and observable academic competences in the Kiswahili language among secondary school students in Mbarara Municipality. The purpose of this study, therefore, was to assess the effect of learner-centred methods of instruction on learners’ observable academic competencies in the Kiswahili language in Mbarara Municipality secondary schools in Uganda. The design adopted in the study was a Quasi-Experimental. Stratified random sampling was used to select 6 schools from 36 schools. The 36 schools were put into 3 categories (strata); highly performing schools, moderate performing schools, and low performing schools as per Uganda National Examinations Board. Simple random sampling was then used to select two schools from each category. The tools used in the study were: the lesson observation schedule and Kiswahili examination tests (pre-test and post-test). Teachers were observed when teaching; before and after training on the use of learner-centred methods of teaching. Learner-centred methods of instruction were used at 34.4% before training the teachers on the use of learner-centered methods and after training the teachers it was used at 85.4%. The study established that there was a significant increase in learners’ observable academic competencies in the Kiswahili language subject. The study therefore recommends that teachers should be trained to adopt and practice more learner-centerd instructional methods to teach the Kiswahili language
Keywords: Learner centered; Instructional Methods; Academic Competencies; Kiswahili